Improvements to the Shaw-Type Absolute Palaeointensity Method - Lloyd, Simon J.; Paterson, Greig A.; Thallner, Daniele; Biggin, Andrew J. (Frontiers in Earth Science, 2021)
Palaeointensity information enables us to define the strength of Earth’s magnetic field over geological time, providing a window into Earth’s deep interior. The difficulties in acquiring reliable measurements are substantial, particularly from older rocks. Two of the most significant causes of experimental failure are laboratory induced alteration of the magnetic remanence carriers and effects relating to multidomain magnetic carriers. One method that has been claimed to overcome both of these problems is the Shaw method. Here we detail and evaluate the method, comparing various selection criteria in a controlled experiment performed on a large, non-ideal dataset of mainly Precambrian rocks. Monte Carlo analyses are used to determine an optimal set of selection criteria; the end result is a new, improved experimental protocol that lends itself very well to the automated Rapid 2G magnetometer system enabling experiments to be carried out expeditiously and with greater accuracy.